Hospital-acquired bacterial infections in COVID-19 intensive care unit: A retrospective cross-sectional study - Mirko Mihalj; Zoran Karlović; Dajana Vladić-Spaić; Manja Spahalić; Katarina Cvitković; Jurica Arapović (Elsevier, 2023)
Background: The aim of this study was to determine the incidence of hospital-acquired infections (HAIs) in patients with SARS-CoV-2 coronavirus (COVID-19) infection admitted to the intensive care unit (ICU), and the most common causing pathogenic microorganisms. Methods: This retrospective study included 535 patients admitted to the COVID-19 ICU of University Clinical Hospital Mostar from July 2020 to December 2021. The results of blood culture, urine culture, and bronchial aspirate samples were analyzed for each patient who met the inclusion criteria. Results: Of a total of 535, 194 (36.2 %) patients had 313 confirmed HAIs at the COVID-19 ICU. The predominant infection was hospital-acquired pneumonia (HAP) (56.2 %), following bloodstream infections (BSI) (23.6 %) and urinary tract infections (UTI) (20.2 %). The most common isolate was multidrug-resistant (MDR) Acinetobacter baumannii causing 50.5 % of HAPs, 33.6 % of BSIs, and 9.6 % of UTIs. Furthermore, Klebsiella pneumoniae was the cause of 22 % of BSI, 22.9 % of UTI, and 17.5 % of HAP. Enterococcus species were the most common isolates of UTIs (43.4 %). Patients with HAIs stayed on average significantly longer in the ICU in comparison with patients without HAIs (12.1 ± 5.5 vs 6.7 ± 3.1 days, p < 0.001). Conclusion: Hospital-acquired infections are common complications in critically ill COVID-19 patients with a predominance of respiratory infections and are also associated with a significantly longer stay in the ICU.